The algebraic moments of vorticity. Theory and numerical tests - Bresiński, Robert; Styczek, Andrzej (Computer Assisted Methods in Engineering and Science, 1995)
The paper presents the method of algebraic vorticity moments. It may be used to solve problems of viscous liquid motion in 2-D and 3-D cases. Its essence lies in the integration of a set of ordinary differentia equations. The unknown functions of those equations defined as , wxmyn dxdy allow to find the vorticity field and next the velocity. We also show a number of 2-D numerical examples.